Insulinomas: Comprehensive Review of Epidemiology, Pathophysiology, Clinical Manifestations, Diagnostic Approaches, and Treatment Options - Rychlewska-Duda, Joanna; Lisiecka, Justyna; Janik, Mateusz; Ufnalska, Barbara; Konarska, Anna; Fabijański, Artur; Machowiak, Anna; Nowak, Michał; Firlej, Wojciech; Dukacz, Adriana Daria (Quality in Sport, 2025)
Pancreatic neuroendocrine tumors (PNETs) are rare endocrine tumors originating from pancreatic cells, constituting 1-2% of pancreatic tumors. The incidence of PNETs has risen from 0.32 to 0.48 per 100,000 people between 2004 and 2021. Among PNETs, insulinomas are the most common type, characterized by excessive insulin production, with an occurrence rate of 1-4 per million people. This review provides a comprehensive analysis of insulinomas, focusing on their epidemiology, pathophysiology, clinical manifestations, diagnostic methods, and treatment strategies. Insulinomas can be sporadic or associated with Multiple Endocrine Neoplasia Type 1 (MEN-1) syndrome, a genetic disorder caused by mutations in the MEN1 gene. MEN-1-associated insulinomas are often diagnosed earlier and may present as multicentric lesions, whereas sporadic insulinomas are typically solitary and benign. Diagnostic approaches include biochemical tests, such as the 72-hour fasting test, and imaging techniques like CT, MRI, and nuclear medicine scans for tumor localization. Surgical resection remains the primary treatment modality, with high success rates for benign tumors, although emerging techniques like endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) offer promising alternatives for small, solitary tumors. Medical management, including medications like diazoxide and somatostatin analogs, is crucial for controlling symptoms in patients not amenable to surgery. Prognosis is generally favorable with surgical intervention, but careful monitoring is required for malignant or metastatic disease. Ongoing research is essential to enhance treatment strategies and improve patient outcomes.